IMPLEMENTASI KEBIJAKAN PEMILIHAN UMUM KEPALA DAERAH TAHUN 2013 DI KOTA PAGARALAM KABUPATEN LAHAT PROVINSI SUMATERA SELATAN - Muhammad Firza (REFORMASI, 2014)
This is a qualitative research with descriptive qualitative research methods. The purpose of this study was to determine how the implementation ofthe policyand community participation to the election. The results showed thatthe level ofparticipationis still lackingdue to thecommunicationbetween actorsas acommunity organizer with stakeholders are not going well, resulting in low levels of participation that leads to thelack of legitimacy ofelected regional heads.